Antioxidant and Anti-inflammatory Potential of Sargassum sp Extract in Lotion Preparations - Safitri, Dwi; Yuliani, Dina; Aldi, M Fardinal; Julfika, Titi; Larasati, Chandrika Eka; Rahman, Ibadur; Jefri, Edwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sargassum sp. is a type of brown algae found in Indonesian marine waters with great potential in the food and pharmaceutical industries. There is antioxidant and anti-inflammatory potential in Sargassum sp. extract so that it makes this type utilised as a lotion preparation. It is necessary to know the potential of Sargassum sp. extract in making lotions. This research uses extraction method to produce Sargassum sp. extract with organic solvent extraction technique, namely alcohol. In addition, the emulsion method was used in the manufacture of lotion preparations. Furthermore, secondary metabolites and anti-inflammatory (irritation) tests were conducted. In addition, the lotion preparation can be evaluated by conducting organoleptic, pH, and homogeneity tests. The results showed that the Sargassum sp. extract contained significant antioxidant compounds, as indicated by a decrease in DPPH absorbance. Sargassum extract contains alkaloid, flavonoid, saponin, and tannin. In addition, lotion preparations containing Sargassum sp. extract also showed a significant decrease in pro-inflammatory cytokine expression in skin cells exposed to UVB radiation. In addition, the irritation test showed negative results with a safety level without causing irritation to the skin. These findings indicate the potential of Sargassum sp. extract in producing lotion preparations with antioxidant and anti-inflammatory effects that can contribute to skin protection from oxidative damage and inflammation.